PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA KANTOR PENGAIRAN KUTACANE - Rila Maufira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The nature of this research is descriptive quantitative. That is researchconducted to determine the value of the independent variable without makingcomparisons or connecting with other variables. The validity test used in thisstudy is intended to ensure how well the instrument measures the concept that should be measured. A valid instrument means that the instrument can be usedto measure accurately and correctly, by using a research instrument that hashigh validity, the research results are able to explain the research problemaccording to the actual situation or event. Reliability tests are carried out todetermine the consistency and accuracy of measurements, if measurements aremade on the same object repeatedly with the same instrument. To assessreliability, Cronbach's Alpha is used which is calculated using spss. Aninstrument has high reliability if the value of Cronbach's Coefficient Alpha >0.6 and Cronbach's Alpha If Item Delete < Cronbach's Coefficient Alpha(Ghozali, 2006:113). Through the results of the normality test of the dataobtained, it is known that the significant value using the residual value throughthe Kolmogorov-Smirnov Z method on spss for all variables X and Y is 0.057 >0.05, so because the significant value is greater than 0.05 it can be said to bedistributed normal. Through data processing in the Coefficients table in the Signcolumn. Above, the significance value is 0.000. Where the value is 0.000 < 0.05.Thus Ho is accepted, which means that there is a significant influence betweenleadership style (X) on employee performance (Y) at the Kutacane irrigationoffice